Choosing the optimal number of generations in the genetic algorithms with binary-real solutions coding - Мочалин, Александр Евгеньевич (Technology audit and production reserves, 2015)
This work is devoted to the problem of choosing the optimal stopping criterion in the transition from the binary coding to the real number coding in genetic algorithms with binary-real representation of solutions in the chromosomes. The main criteria for stopping the modern genetic algorithms based on the phenotype or genotype of individuals are considered. Their advantages and disadvantages are presented. The main purpose of research is to develop a new intermediate stopping criterion of genetic algorithm with binary-real coding. The developed criteria based on the fact that the values of best chromosomes change within a certain low threshold for some generations. New intermediate stopping criterion allows the efficient spending computing resources using genetic algorithms with binary-real coding. A comparative efficiency analysis of the new stopping criterion of the transition from one type of coding to another in the optimization of complex multi-extremal function is conducted. Efficiency analysis allowed forming recommendations for the selection of the threshold values in the calculation of a new stopping criterion. The same analysis showed inefficient use of population convergence criterion as an intermediate stopping criterion. The advantages of the new criterion above the criteria based on the fact that the value of the best chromosomes is constantly for several generations are presented.